Causes and methods to estimate cryptic sources of fishing mortalitya. Issue 4 (6th June 2013) - Gilman, E.; Suuronen, P.; Hall, M.; Kennelly, S.
<x xml:space="preserve">Abstract</x> Cryptic, not readily detectable, components of fishing mortality are not routinely accounted for in fisheries management because of a lack of adequate data, and for some components, a lack of accurate estimation methods. Cryptic fishing mortalities can cause adverse ecological effects, are a source of wastage, reduce the sustainability of fishery resources and, when unaccounted for, can cause errors in stock assessments and population models. Sources of cryptic fishing mortality are (1) pre‐catch losses, where catch dies from the fishing operation but is not brought onboard when the gear is retrieved, (2) ghost‐fishing mortality by fishing gear that was abandoned, lost or discarded, (3) post‐release mortality of catch that is retrieved and then released alive but later dies as a result of stress and injury sustained from the fishing interaction, (4) collateral mortalities indirectly caused by various ecological effects of fishing and (5) losses due to synergistic effects of multiple interacting sources of stress and injury from fishing operations, or from cumulative stress and injury caused by repeated sub‐lethal interactions with fishing operations. To fill a gap in international guidance on best practices, causes and methods for estimating each component of cryptic fishing mortality are described, and considerations for their effective application are identified. Research priorities to fill gaps in understanding the causes and estimating cryptic mortality are highlighted.